2020
DOI: 10.1155/2020/9380965
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Prevents Osteoarthritis of High-Fat Diet-Induced Obese Rats

Abstract: The effects of acupuncture on osteoarthritis (OA) pathogenesis have been demonstrated in vitro and in animal models. However, the potential for acupuncture to mediate protective effects on obese-induced OA has not been examined. Here, we investigated the effects of different acupuncture patterns on OA pathogenesis in high-fat diet- (HFD-) induced obese rats. After 12-week diet-induced obesity, obese rats were treated with three acupuncture protocols for 2 weeks, including ST36, GB34, and ST36+GB34. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 50 publications
1
26
0
1
Order By: Relevance
“…As one of the complex ecosystems in the gastrointestinal tract, the intestinal flora is related to metabolism-related diseases and multi-system diseases ( Di Segni et al, 2018 ). Acupuncture was proved to alleviate obesity-related lipid metabolism disorders and intestinal microbiota disorders ( Gao et al, 2020 ; Xie et al, 2020 ). For example, electroacupuncture promoted the diversity of the gut microbiota of obese mice, thus reducing body weight ( Dou et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…As one of the complex ecosystems in the gastrointestinal tract, the intestinal flora is related to metabolism-related diseases and multi-system diseases ( Di Segni et al, 2018 ). Acupuncture was proved to alleviate obesity-related lipid metabolism disorders and intestinal microbiota disorders ( Gao et al, 2020 ; Xie et al, 2020 ). For example, electroacupuncture promoted the diversity of the gut microbiota of obese mice, thus reducing body weight ( Dou et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Butyricimonas is a beneficial bacteria that can produce SCFA to reduce inflammation. Studies have shown that increased relative abundance of Butyricimonas is associated with improved metabolic parameters and insulin resistance in mice (38). Taken together, these results indicate that CRP extract improved the gut microbiome in AZT-treated juvenile mice and improved glycolipid metabolism disorder in adulthood under HFD feeding.…”
Section: Discussionmentioning
confidence: 61%
“…EA inhibits the pro-inflammatory transformation of intestinal microbiota by increasing the ratio of Bacteroidetes/ Firmicutes, and promotes the recovery of the relative abundance of Clostridium, Ackermann, Butyricimonas, and Lactococcus. 93 EA at ST35 and Ex-LE4 also reduces the expression of MMP-3 and MMP-13 in chondrocytes, regulates cartilage matrix metabolism, reduces degradation of type II collagen, and relieves knee arthritis. 95 The Endocannabinoid System…”
Section: Dovepressmentioning
confidence: 97%
“…The combined effect of two acupoints was found to be better than that of GB34 alone. 93 It was previously reported that serum from TNF-α-treated chondrocytes, treated with EA serum (EAS), significantly reduces IL-1β levels and enhances chondrocyte viability by inhibiting RAS, RAF, MEK1/2, and P-ERK1/2 protein expression. 94 This study used post-acupuncture serum in the treatment regimen.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation